C-reactive protein as a prognostic marker in coronavirus disease-2019 - Sarwat, Tarana; Kumar, Devendra; Singh, Neeraj Pal; Kakru, Dalip (Eastern Journal of Medical Sciences, 2021)
Background: Coronavirus disease-2019 (COVID-19) is a recently emerged viral disease, for which there’s currently no definitive treatment. It is, therefore, necessary to determine biomarkers to know the extent of disease severity so that timely action can be taken to reduce mortality. We aimed to determine the usefulness of C-reactive protein (CRP) levels in assessing COVID-19 disease severity and correlate them with mortality due to the same. Methods: Data for COVID-19 were retrospectively collected and analyzed from May 2020 to October 2020. The CRP value was correlated with disease severity using Karl Pearson’s correlation coefficient. A logistic regression model was adopted to analyze the association between mortality and related factors. Results: Out of 642 patients enrolled, 22 died while 620 recovered. Most of the non-survivors were male. Multivariate analysis showed that age, diabetes, hypertension, and CRP values were significantly associated with mortality. CRP showed a strong positive correlation with disease severity and, hence, mortality. Conclusion: In patients with COVID-19, CRP correlated with disease severity and tended to be a good predictor of adverse outcome.